HUBUNGAN PENGEMBANGAN DIRI DAN MINAT KERJA DENGAN KESIAPAN KERJA - Yuniyanti, Yuniyanti (JURNAL LENTERA BISNIS, 2021)
In an effort to increase maximum work readiness, students do not only fulfill the input and output aspects, but what is more important is the process aspect, the process in question is self-development and work interest processes. Both of these things have a high level of importance compared to other processes. The right educational process will be carried out by educational institutions in order to produce valuable and work-ready human resources, so that every student who graduates will be able to develop a career according to their competencies. Based on this, educational institutions must be able to provide confidence to stakeholders that their institutions are qualified in carrying out real educational goals. The implementation of self-development and work interest is a real solution in fulfilling expectations to synergize with each other in an effort to increase student work readiness. Students have harmony between physical, mental and experience abilities with individual capacities in preparing themselves for the work industry so that in the end they are able to carry out certain activities related to work according to the targets that have been set with full responsibility and professionalism.Key words:  Self Development, Work Interest and Work Readiness